Flexible Symbiotic Associations of Symbiodinium With Five Typical Coral Species in Tropical and Subtropical Reef Regions of the Northern South China Sea - Gong, Sanqiang; Chai, GuangJun; Xiao, Yilin; Xu, Lijia; Yu, Kefu; Li, Jinlong; Liu, Fang; Cheng, Hao; Zhang, Fengli; Liao, Baolin; Li, Zhiyong (Frontiers in Microbiology, 2018)
The coral symbiont Symbiodinium plays important roles in the adaptation of coral to environmental change. However, coral-Symbiodinium symbiotic associations are not well-understood in the South China Sea (SCS) whilst considering environmental factors and host taxa. In this study, next-generation sequencing of the ITS2 marker gene was used to explore the symbiotic associations between Symbiodinium and five typical coral species across tropical and subtropical reef regions of the SCS. The results showed that Acropora sp., Galaxea fascicularis, Platygyra lamellina and Sarcophyton glaucum exhibited distinct Symbiodinium compositions between tropical and subtropical reef regions, while Porites lutea has stable Symbiodinium compositions. More heterogeneous Symbiodinium compositions among different coral species were observed in the tropical region, but there was not statistically significant differences in Symbiodinium compositions among different coral species in subtropical reef regions. There was a correlation between the Symbiodinium compositions and environmental factors, except for the composition of P. lutea. Symbiodinium subclades D1, D2, C71, C71a, C21, C3b, and C161 were primarily explained by the seawater temperature, nitrate, ammonia and phosphate; several host-specific Symbiodinium subclades (e.g., C15, C15.6 and C91) were observed in P. lutea, as well. This study’s findings regarding the relationship of Symbiodinium diversity with coral hosts and the environment are helpful for elucidating corals’ adaptation to global climate change and anthropogenic disturbance.